2012
DOI: 10.1016/j.chiabu.2011.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Associations among childhood sexual abuse, language use, and adult sexual functioning and satisfaction

Abstract: To better understand the link between childhood sexual abuse (CSA) and adult sexual functioning and satisfaction, we examined cognitive differences between women with (N = 128) and without (NSA, N = 99) CSA histories. We used the Linguistic Inquiry Word Count, a computerized text analysis program, to investigate language differences between women with and without CSA histories when writing about their daily life (neutral essay) and their beliefs about sexuality and their sexual experiences (sexual essay). Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
34
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 46 publications
7
34
2
Order By: Relevance
“…In the same study, abused women used intimacy words (e.g., loving, arousable, warm) more than nonabused women in the sexual essay, perhaps suggesting a greater link between intimacy and sex for women with a history of CSA. In this study there were no differences in the use of sexual words (e.g., erection, sex, kiss) in the sexual essay between the two groups of women (Lorenz & Meston, 2012). …”
contrasting
confidence: 55%
See 2 more Smart Citations
“…In the same study, abused women used intimacy words (e.g., loving, arousable, warm) more than nonabused women in the sexual essay, perhaps suggesting a greater link between intimacy and sex for women with a history of CSA. In this study there were no differences in the use of sexual words (e.g., erection, sex, kiss) in the sexual essay between the two groups of women (Lorenz & Meston, 2012). …”
contrasting
confidence: 55%
“…Depression is an important risk factor for the development of sexual problems in women both with and without a history of CSA (Bodenmann & Ledermann, 2008; Trudel & Goldfarb, 2010); therefore, this relationship may simply reflect the impact of depression on sexual health. Prior research on abused and nonabused women’s word use has documented that positive emotion word use, but not negative emotion word use, is associated with sexual function (Lorenz & Meston, 2012). In the current study, however, we found that for women with sexual abuse histories, decreases in negative emotion word use predicted better sexual function and sexual satisfaction, and changes in positive emotion word use did not predict changes in sexual outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsic methods in sex research are less direct than self-report measures and often involve tests of reaction times (Mouras et al, 2003), implicit associations (Meston & Heiman, 2000), physiological responses (Meston & Gorzalka, 1996a, 1996b) as well as general unconditioned responses, like cortisol levels (Meston & Lorenz, 2013). A few studies in this field have used the Linguistic Inquiry and Word Count Software (LIWC; Pennebaker, Booth, & Francis, 2001) to analyze themes within bodies of text (Lorenz & Meston, 2012; Pulverman, Lorenz, & Meston, 2015). The LIWC program operates by tallying the frequencies of words that fall within discrete, experimenter-defined categories.…”
mentioning
confidence: 99%
“…They wrote on a computer, and were instructed to close their essays at the end of the 30-min period to ensure confidentiality. After the study was completed, these essays were verified for compliance with treatment prompts; no essay was found to be noticeably off-prompt (for more detail, see Lorenz and Meston 2012). …”
Section: Methodsmentioning
confidence: 99%